2023
DOI: 10.1007/s00431-023-04974-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects and individual response of continuous and interval training on adiponectin concentration, cardiometabolic risk factors, and physical fitness in overweight adolescents

Abstract: ObjectiveStudy aimed to evaluate the effect and individual responsiveness after 12-weeks of high-intensity interval training (HIIT) and moderate-intensity of continuous training (MICT) on adiponectin, cardiometabolic risk factors and physical tness in overweight adolescents. MethodsParticipated 52 adolescents, both sexes, 11 and 16 years-old: HIIT (n = 13), MICT (n = 15) and control group (CG, n = 24). Body mass, height, waist circumference (WC), fat mass (FM), fat-free mass (FFM), blood pressure, high-density… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been documented ( 44 ) that HIIT exhibits superior efficacy in reducing risk factors associated with skeletal sarcopenia and mitigating the morphological and functional deterioration linked to this condition, surpassing the benefits of resistance training. Notably, compared to the MICT group, the HIIT group experienced a significant reduction in BMI and a substantial increase in peak VO 2 , according to the study by Tadiotto et al ( 45 ). Based on the results of the present meta-analysis, we therefore hypothesize that HIIT is preferable to MICT for increasing peak VO 2 in HFrEF patients with a low.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, it has been documented ( 44 ) that HIIT exhibits superior efficacy in reducing risk factors associated with skeletal sarcopenia and mitigating the morphological and functional deterioration linked to this condition, surpassing the benefits of resistance training. Notably, compared to the MICT group, the HIIT group experienced a significant reduction in BMI and a substantial increase in peak VO 2 , according to the study by Tadiotto et al ( 45 ). Based on the results of the present meta-analysis, we therefore hypothesize that HIIT is preferable to MICT for increasing peak VO 2 in HFrEF patients with a low.…”
Section: Discussionmentioning
confidence: 87%
“…One study scored below 4. Blinding techniques ranged from 0 to 3 in this study, with only one study scoring 3 and four scoring 1; Fifteen studies scored 0. www.nature.com/scientificreports/ Tadiotto et al conducted a 12-week HIIT and MIIT intervention study and found significant reductions in (body mass index) BMI-z, (waist-to-height ratio) WHtR, and LDL-c in HIIT 28 . Benson et al compared the effects of high-intensity progressive resistance training (PRT) on body composition in obese children and showed that an 8-week PRT intervention resulted in significant improvements in adiposity, percentage body fat, and body mass index 34 .…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…Each exercise lasts 60 min, with walking and running at different intensities crossed Tadiotto et al 28 HIIT reduces BMI-z, waist-to-height ratio, and improves physical fitness 52 adolescents (11)(12)(13)(14)(15)(16) Ramirez-Velez etal. 30 Based on the LIPE and groups, several levels of circulating inflammation can be significantly altered 95 adolescents (M = 13.5 ± 1.6 years) Randomly assigned School-based exercise programs.…”
Section: Randomly Assigned Cycling Interventions Of Varying Intensitymentioning
confidence: 99%
“…Seven studies were interventions with interval training of varying intensities. Four studies have shown that high-intensity interval training (HIIT) is effective in reducing visceral fat, while moderateintensity interval training (MICT) reduces body fat percentage (BF%)21,24,40,43 . One study showed that high-intensity interval training had a moderate effect on improving body composition in adolescents41 .…”
mentioning
confidence: 99%
“…One study showed that high-intensity interval training had a moderate effect on improving body composition in adolescents41 . The study by Tadiotto et al showed that high-intensity interval training reduced body mass index, and waist-toheight ratio, and improved physical tness21 . In addition, four studies used aerobic exercise of varying intensities.…”
mentioning
confidence: 99%